Developing critical thinking competence through using the exercise in teaching chemistry in high school - Trinh , Le Hong Phuong (Journal of Technical Education Science, 2016)
The usage of the exercises in teaching chemistry in high school is one of the many viable methods to help the development of critical thinking competence proceed faster, easier and more efficient. This report introduces the using of chemistry exercises in order to develop cric- tical thinking competence based on the research results about: the concept, the structure, the manifestations of critical thinking and in compliance with the 5 principles and 10 steps of the process of developing competence.